Motivation and satisfaction of marathon volunteers: How important is volunteers' level of running experience?. Issue 1 (2nd January 2017) - Ma, Xiao; Draper, Jason
ABSTRACT: Special events such as marathons frequently depend on volunteers who may have various motivations for volunteering. The purpose of this study is to examine the motivations of volunteers of marathons, differences in motivation by demographics, level of running experience, and relationships with satisfaction. The results reveal differences in the love of sport volunteer motivation by the level of running experience. In addition, the level of running experience variable, which is unique in volunteer motivation studies, moderates the relationships between motivations and satisfaction, suggesting events such as marathons could benefit from recruiting volunteers who themselves participate in the event activity.